2002
DOI: 10.1590/s1677-04202002000300004
|View full text |Cite
|
Sign up to set email alerts
|

Portable chlorophyll meter for the quantification of photosynthetic pigments, nitrogen and the possible use for assessment of the photochemical process in Carica papaya L.

Abstract: The techniques utilized to extract chlorophyll from plant materials are destructive and based on methods that use organic solvents. This study proposes the non-destructive quantification of chlorophyll and nitrogen concentration using a portable chlorophyll meter (SPAD-502). Further, was possible to establish relationships between chlorophyll fluorescence and SPAD-502 values. This methodology could save time, space and resources, and could be used for analysis of the photosynthetic processes. Papaya leaves (So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(18 citation statements)
references
References 35 publications
(32 reference statements)
0
15
0
3
Order By: Relevance
“…Valores de 0,800 ± 0,05 correspondem à máxima eficiên-cia no uso de energia no processo fotoquímico (Björkman & Demmig, 1987;Bolhàr-Nordenkampf et al, 1989;Torres Neto et al, 2002) e valores inferiores a 0,750 indicam situação de estresse e, portanto, redução do potencial fotossintético da planta (Maxwell & Johnson, 2000;Araújo et al, 2004).…”
Section: Eficiência Quântica Do Fotossistema II (Eficiência Fotossintunclassified
See 2 more Smart Citations
“…Valores de 0,800 ± 0,05 correspondem à máxima eficiên-cia no uso de energia no processo fotoquímico (Björkman & Demmig, 1987;Bolhàr-Nordenkampf et al, 1989;Torres Neto et al, 2002) e valores inferiores a 0,750 indicam situação de estresse e, portanto, redução do potencial fotossintético da planta (Maxwell & Johnson, 2000;Araújo et al, 2004).…”
Section: Eficiência Quântica Do Fotossistema II (Eficiência Fotossintunclassified
“…A medição da fluorescência da clorofila pode ser usada para revelar informações sobre os estádios de desenvolvimento de plantas (Bacarin & Mosquin 2002), para comparar genótipos (Portes & Magalhães, 1993;Campostrini & Maestri, 1998) e é usada, também, para investigar danos causados no aparato fotossintético, por diversas causas de estresses (Smille & Not, 1982;Strant & Oquist, 1988;Havaux et al, 1988;Torres Neto et al, 2002;El-Sheekh, 1993). Esta variável é uma significativa informação da eficiência fotoquímica do processo fotossintético (Torres Neto et al, 2002) Desta forma, as aferições da fluorescência e do potencial hídrico de espécies da Caatinga, que constituem objetivos deste trabalho, podem contribuir para o entendimento do processo evolutivo dessas plantas sob condições adversas, permitindo caracterizar as diferenças fisiológicas nas duas estações características da Região Nordeste, o período chuvoso e o período de estiagem.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Changes in chlorophyll-to-carotenoid ratios are therefore potentially sensitive indicators of oxidative damage (Hendry and Price, 1993). The loss of these pigments may also be considered as an indicator of water deficiency (Hendry and Price, 1993) and senescence (Lin and Ehleringer, 1982b;Torres-Netto et al, 2002Castro, 2005). Castro (2005) found that F v /F m and the physiological state of the photosynthetic apparatus (F 0 /F m ) in PSII were unrelated to chlorophyll content for 'Golden' and 'Sunrise Solo' when chlorophyll content was adequate but there was a correlation at reduced chlorophyll levels.…”
Section: Ecophysiology Of Papayamentioning
confidence: 99%
“…Hand-held Chl meters have been shown to be accurate for estimating foliar Chl and nitrogen contents in several plant species (Torres-Netto et al 2002, Chang and Robison 2003, Marenco et al 2009). Hand-held devices such as the SPAD-502 Chl meter measure light transmittance at two wavelengths corresponding to red and far-red, and transform this data to SPAD values (Markwell et al 1995).…”
Section: Introductionmentioning
confidence: 99%